2023
DOI: 10.1186/s12967-023-04141-3
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 promotes tumour progression by remodelling the mitochondrial network in cervical cancer

Abstract: Background Cervical cancer remains one of the most prevalent cancers worldwide. Accumulating evidence suggests that specificity protein 1 (Sp1) plays a pivotal role in tumour progression. The underlying role and mechanism of Sp1 in tumour progression remain unclear. Methods The protein level of Sp1 in tumour tissues was determined by immunohistochemistry. The effect of Sp1 expression on the biological characteristics of cervical cancer cells was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…As highlighted in the introduction part, SP1 serves as a transcription factor that plays a pivotal role in various biological processes, including cell proliferation, differentiation, and apoptosis 13 . Studies have also shown that SP1 promotes chemotherapeutic resistance in ovarian cancer and regulates glucose metabolism in cervical cancer 14,15 . We hypothesized that GBP1 might influence the progression of tumours by affecting SP1.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As highlighted in the introduction part, SP1 serves as a transcription factor that plays a pivotal role in various biological processes, including cell proliferation, differentiation, and apoptosis 13 . Studies have also shown that SP1 promotes chemotherapeutic resistance in ovarian cancer and regulates glucose metabolism in cervical cancer 14,15 . We hypothesized that GBP1 might influence the progression of tumours by affecting SP1.…”
Section: Resultsmentioning
confidence: 97%
“…For instance, SP1 induces the expression of MCF2L‐AS1, facilitating the activation of the IGF2/MEK/ERK pathway via interaction with IGF2BP1, thereby promoting cisplatin resistance in ovarian cancer 14 . Additionally, SP1 has been implicated in cervical tumorigenesis by modulating the mitochondrial network and reshaping glucose metabolism 15 . Despite these insights from other cancer types, research on the role of SP1 in cSCC remains limited and warrants further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, various types of addiction to specific transcriptional programs and/or kinase activities appear to operate in specific subsets of cancer and are thought to deeply contribute to cancer pathogenesis [77,78]. Interestingly, when a more accurate and stringent analysis was performed on the regulated target genes of these two candidate miRNAs, Mienturnet analysis followed by MetaCore process networks revealed the presence of important central hubs, including the transcriptional factors SP1 (specificity protein 1), RXRA (retinoid X receptor alpha), and BMI-1 (polycomb ring finger proto-oncogene) and the epidermal growth factor receptor kinase EGFR, with multiple roles in breast cancer development and progression [79][80][81][82]. Moreover, Metacore gene enrichment analysis indicated the involvement of the 18 target genes in cell cycle transition from G2 to M, the follicle-stimulating hormone (FSH) beta signaling pathway, androgen receptor signaling cross-talk, NOTCH signaling, ESR1 nuclear pathway and signaling, and EMT among the top enriched processes.…”
Section: Discussionmentioning
confidence: 99%
“…The same observations are also done with the transcription factor TRIM28 who is generally involved in upregulation of cancer expression in tissues which correlates with worse overall patient survival 35 , so TRIM28 could supports kidney cancer progression. Most transcriptional factor as TCF3 36 , ERG 37 , SP1 38,39 contribute to the pathogenesis of human cancers. Several peptides have been identified with high target prediction probabilities, notably 13.…”
Section: Discussionmentioning
confidence: 99%